Electric Wheelchairs for the Disabled - Nguyễn Hữu Hường; Nguyễn Lê Duy Khải; Nguyễn Đình Hùng; Trần Đăng Long (Journal of Technical Education Science, 2012)
This paper introduces the results of reseach, design and manufacturing of prototypical electric wheelchairs for the disabled and the elderly based on manual wheelchairs. They can be used indoors and outdoors, in suburban and rural areas, and in narrow areas. The electric wheelchairs are controlled by the electrical system, and easy to connect. Characteristics of the model are: simple structure, easy to manufacture, easy maintenance and repair. The electric wheelchairs can be mass-produced in Vietnam for the disabled and the elderly at low price.